Low intensity light treatment improves purple kale (Brassica oleracea var. sabellica) postharvest preservation at room temperature - Bárcena, Alejandra (2019)
Purple Kale is a vegetable of the Brassicaceae family whose are popularly consumed in recent years due to their high level of healthy components. For consumption, matures leaves are harvested and postharvest senescence is induced. Changes in color leaves due to chlorophyll degradation are the main visible symptoms of postharvest senescence, but there are other changes that affect the nutritional quality of kale. The aim of this study was to investigate if low intensity light pulses could be used to delay postharvest senescence of purple kale stored at room temperature. Daily treatments with 1 h pulses of white or red light were performed. Irradiated samples had approximately 40% higher chlorophyll and protein and more of 20% higher antioxidant capacity and soluble sugar content than control samples regardless of light quality used in treatment (white or red). Both light treatments improve the appearance and quality of kale during storage at room temperature.